Tackling NCDIs in Cambodia : An Opportunity for Inter - and Itra-Sectoral Synergies - World Bank Group (Washington, DC, 2015)
Non-communicable diseases (NCDs) are a set of chronic diseases, including cardiovascular disease, cancer, chronic respiratory disease, and diabetes that are on the rise in Cambodia. Meanwhile, injuries include those due to traffic accidents, which are becoming a major source of mortality and morbidity in Cambodia. NCDs are increasing in Cambodia as a result of smoking, unhealthy diet, harmful use of alcohol, and physical inactivity, all resulting in a sharp increase in the rates of obesity and high blood pressure. NCDs are affecting Cambodians in their productive years. Over half men and over a third of women dying from NCDs are younger than 60 years. The high cost of long-term health care and medicines, along with loss of income, pushes many Cambodian families deeper into poverty. It also overburdens the country's health system, constraining efforts to improve maternal and child health and tackle infectious diseases. Because of the nature of NCDs, which are rooted in multiple causes, strengthening the health system alone will not reduce the burden of NCDs. Many of the actions needed to prevent and control these diseases require the participation of numerous ministries and government agencies, as well as the private sector. For Cambodians to continue enjoying the fruits of economic growth, a strong commitment by the government, the people, and the international community is becoming increasing important. Improved coordination among all ministry of health (MOH) task forces will maximize financial and human resources and help implement priority NCDI-related interventions as part of, and not separate from, other ongoing programs. The application of the measures will benefit from clear procedures for joint planning, programming, budgeting, training, reporting, and monitoring and evaluation (M and E) of all programs.